Integrating Online Gamification into Islamic Religious Education in Indonesian Elementary Schools - Amri, Muhammad Farizal (PAI RAFAH, 2025)
The advancement of educational technology has opened new opportunities for digital innovation in Islamic Religious Education (IRE). This study aims to analyze the implementation of online gamification in IRE at SD Negeri 3 Ngadirgo, Semarang, and its influence on students’ engagement, motivation, and moral internalization. Using a qualitative descriptive approach, data were collected through classroom observations, interviews with teachers, students, and the principal, as well as an analysis of instructional documents. The findings indicate that digital platforms such as Wordwall, Quizizz, Canva, and Wheel of Names effectively enhance students’ enthusiasm, participation, and moral awareness, particularly values of honesty, responsibility, and ukhuwah islamiyah (Islamic brotherhood). Teachers demonstrated pedagogical readiness by designing game-based lessons aligned with the moral objectives of IRE. Institutional support, including digital infrastructure, teacher collaboration, and visionary leadership, further strengthened the sustainability of innovation. This study concludes that online gamification can serve as a modern form of ta’dib (moral cultivation), integrating digital creativity with spiritual formation. It contributes to the development of the digital faith pedagogy framework, emphasizing that technology, when guided by ethical and spiritual purposes, can become a catalyst for value-based learning in Islamic education.